Pogledi študentov pedagogike na obvezno praktično usposabljanje - Rus, Danijela (Revija za elementarno izobraževanje, 2013)
Views of Pedagogy Students on Mandatory Work Placement. In the first part of this discourse we discuss the general importance of undergraduate student placement and we further focus on compulsory (unpaid) work placement students of pedagogy must undergo as part of the programme. During work placement in a school or an institution, a student of pedagogy must obtain different competences which are related to work within the educational institution and to his or her own expertise. A mentor plays an essential role in this process, introducing students to their tasks, drawing up individual work plans, providing proper observation of the process and encouraging involvement in daily activities taking place in the respective school or institution. In the second part of the discourse, we introduce the results of a survey which provides an insight into what students feel a good school educator should be like and into their expectations prior to starting work placement. Moreover, it gives students’ assessments of the characteristics they developed during their work placement and those they developed with the help of a mentor afterwards.
Keywords: work placement; study of pedagogy; competences; mentoring